2019
DOI: 10.5045/br.2019.54.2.144
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of methylation pattern changes in the IKZF1 promoter in patients with childhood B-cell acute lymphoblastic leukemia

Abstract: Background Ikaros family zinc finger 1 (IKZF1) is a transcription factor with an important role in controlling hematopoietic proliferation and function, particularly lymphoid cell differentiation. It was previously shown that various mechanisms and expression patterns of Ikaros are linked to a variety of cancers. We hypothesized that aberrant methylation (hypomethylation) of the IKZF1 promoter region might be one of the causes of B-cell acute lymphoblastic leukemia (B-ALL). In B-ALL patients, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…A recent study by Rahmani et al suggested that, in B-ALL patients, overexpression of IKZF1 may contribute to B-cell differentiation arrest and proliferation induction. Therefore, when investigating the methylation status of CpG islands in the promoter region of IKZF1 in B-ALL cells of children, a hypomethylation pattern of the gene promoter was observed in 96% of B-ALL samples [ 97 ].…”
Section: Ikzf1 Dysregulation In All: a Mean “Hater”mentioning
confidence: 99%
“…A recent study by Rahmani et al suggested that, in B-ALL patients, overexpression of IKZF1 may contribute to B-cell differentiation arrest and proliferation induction. Therefore, when investigating the methylation status of CpG islands in the promoter region of IKZF1 in B-ALL cells of children, a hypomethylation pattern of the gene promoter was observed in 96% of B-ALL samples [ 97 ].…”
Section: Ikzf1 Dysregulation In All: a Mean “Hater”mentioning
confidence: 99%
“…Ikaros activities are thought to be regulated by post-translational phosphorylation, small ubiquitin-related modifier (SUMOylation), and ubiquitination ( Sridharan and Smale, 2007 ). Besides, the hypomethylated pattern of CpG island in the IKZF1 promoter region may be the basis of abnormal Ikaros expression patterns associated with malignant tumors ( Chen et al, 2019 ; Rahmani et al, 2019 ). SUMOylation interferes in the interaction of Ikaros with transcriptional co-repressors SIN3A, SIN3B, Mi-2β, and CtBP and weakens the inhibitory activity of Ikaros ( Gómez-del Arco et al, 2005 ).…”
Section: Ikaros Family Signalingmentioning
confidence: 99%
“…Childhood acute leukemia (AL) is the most common malignant tumor that invades the blood system of children. It is also the malignant tumor of children with the highest incidence rate, which seriously threatens the life and health of children (1)(2)(3). At present, the pathogenesis of childhood AL remains unclear.…”
Section: Introductionmentioning
confidence: 99%